The performance of split and integrated types of air-source heat pump water heaters in South Africa - Stephen Loh Tangwe (Journal of Energy in Southern Africa, 2018)
Renewable energy technologies that can provide optimum and cost-effective energy savings to mitigate global warming, energy crisis and to achieve energy efficiency continue to be of paramount importance. The present study focused on identifying critical parameters such as the volume of hot water drawn off; ambient temperature; relative humidity; refrigerant temperatures at the inlet and outlet of the compressor and condenser; and deterministic quantities such as time used, power consumption and coefficient of performance (COP) as indicators to benchmark the performance of both the split and integrated types of air-source heat pump (ASHP) water heaters. The basis for analysis was on two predominant scenarios: first-hour heating rating and the heating cycle due to controlled volume of hot water drawn-off wherein both the integrated and split types ASHP water heaters experienced vapour compression refrigeration cycles. A data acquisition system was constructed and implemented to monitor the performance of both systems. The results obtained during summer season showed that, under the scenario of 150 L hot water withdrawal, the average COP of the systems was 3.18 and 2.85 for the split and integrated types respectively. The average power consumed was 1.29 (split type) and 0.85 kW (integrated type). The times of operation were 84 minutes (split type) and 138 minutes (integrated type).